2019
DOI: 10.3390/cancers11030286
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Role of SOX2 as an Early Predictor of Cancer Risk in Patients with Laryngeal Precancerous Lesions

Abstract: The SOX2 gene located at 3q26 is frequently amplified and overexpressed in multiple cancers, including head and neck squamous cell carcinomas (HNSCC). The tumor-promoting activity and involvement of SOX2 in tumor progression has been extensively demonstrated, thereby emerging as a promising therapeutic target. However, the role of SOX2 in early stages of tumorigenesis and its possible contribution to malignant transformation remain unexplored. This study investigates for the first time SOX2 protein expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…However, strikingly, a subset of HNSCC patients (33.3%) harbored high expression of NANOG and SOX2 in histologically normal mucosa with comparable levels to the matched tumor. This finding reflects the early occurrence of altered NANOG and SOX2 expression in head and neck carcinogenesis, also frequently detected in precancerous lesions [ 23 , 27 , 34 ], plausibly triggered by continuous exposure of the epithelial mucosa to tobacco-related carcinogens. In line with this, it has been demonstrated that nicotine plays a critical role in the development of tobacco-induced cancers by increasing the expression of various CSC markers NANOG, OCT4, CD44, and BMI-1 and regulating CSC properties and tumorigenic potential in HNSCC models in vitro and in vivo [ 35 ].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, strikingly, a subset of HNSCC patients (33.3%) harbored high expression of NANOG and SOX2 in histologically normal mucosa with comparable levels to the matched tumor. This finding reflects the early occurrence of altered NANOG and SOX2 expression in head and neck carcinogenesis, also frequently detected in precancerous lesions [ 23 , 27 , 34 ], plausibly triggered by continuous exposure of the epithelial mucosa to tobacco-related carcinogens. In line with this, it has been demonstrated that nicotine plays a critical role in the development of tobacco-induced cancers by increasing the expression of various CSC markers NANOG, OCT4, CD44, and BMI-1 and regulating CSC properties and tumorigenic potential in HNSCC models in vitro and in vivo [ 35 ].…”
Section: Discussionsupporting
confidence: 63%
“…We have recently demonstrated that expression of NANOG and SOX2 plays a relevant role in early stages of laryngeal tumorigenesis. The expression of both proteins was found to increase in patients with precancerous lesions and, more importantly, strongly predicted the risk of progression to invasive carcinoma [ 23 , 27 ]. In addition, both factors have been involved in the epithelial to mesenchymal transition.…”
Section: Discussionmentioning
confidence: 99%
“…30 SOX2 is frequently expressed in LCA and promises to play a predictive role in LCA diagnosis, functioning in promoting LCA cell ability of migration and invasion. 31,32 KDM5B promoted SOX2 expression in LCA cells in the present work. KDM5B and SOX2 are closely correlated in the regulation of atypical teratoid/rhabdoid tumor.…”
Section: Dovepresssupporting
confidence: 63%
“…Female NOD/SCID mice of 6-7 weeks old (Janvier Labs, St Berthevin, France) were inoculated subcutaneously (s.c.) as described [36]. In experiments aimed to evaluate the effect of anti-tumor drugs, mice with tumor xenografts with a volume of approximately 300 mm 3 were randomly assigned to receive the following intravenous treatments: vehicle (saline, every 7 days up to 3 doses), EC-8042 (18 mg/Kg; every 3/4 days up to 5 doses), trabectedin (0.15 mg/Kg; every 7 days up to 3 doses), doxorubicin (4 mg/Kg; every 7 days up to 3 doses) or paclitaxel (20 mg/Kg; every 7 days up to 3 doses). Treatment schedules were optimized according to the therapeutic window of the different drugs [36][37][38].…”
Section: In Vivo Tumor Growthmentioning
confidence: 99%
“…A common characteristic of CSC subpopulations is the overexpression of transcription factors responsible for maintenance of the stem cell phenotype in embryonic and adult stem cells like SOX2 (Sex-determining region Y-box protein 2) or OCT4 (POU5F1, POU Class 5 Homeobox 1) [2]. Subpopulations expressing these pluripotency factors have been correlated with tumor progression, drug resistance and the presence of hierarchically organized CSCs in several types of tumors [3][4][5][6][7][8]. In sarcomas, SOX2 has been found overexpressed in CSCs from different subtypes [9][10][11][12][13][14][15][16][17][18] and was described to play specific pro-tumorigenic roles in osteosarcoma [19][20][21].…”
Section: Introductionmentioning
confidence: 99%